The SET Domain Is Essential for Metnase Functions in Replication Restart and the 5’ End of SS-Overhang Cleavage - Kim, Hyun-Suk (PLoS One, 2015)
Metnase (also known as SETMAR) is a chimeric SET-transposase protein that plays essential role(s) in non-homologous end joining (NHEJ) repair and replication fork restart. Although the SET domain possesses histone H3 lysine 36 dimethylation (H3K36me2) activity associated with an improved association of early repair components for NHEJ, its role in replication restart is less clear. Here we show that the SET domain is necessary for the recovery from DNA damage at the replication forks following hydroxyurea (HU) treatment. Cells overexpressing the SET deletion mutant caused a delay in fork restart after HU release. Our In vitro study revealed that the SET domain but not the H3K36me2 activity is required for the 5’ end of ss-overhang cleavage with fork and non-fork DNA without affecting the Metnase-DNA interaction. Together, our results suggest that the Metnase SET domain has a positive role in restart of replication fork and the 5’ end of ss-overhang cleavage, providing a new insight into the functional interaction of the SET and the transposase domains.